TYPES OF IDIOMS AND STRATEGIES IN TRANSLATING IDIOMS IN THE NOVEL THE GIRL ON THE TRAIN BY PAULA HAWKINS - Delia Imaniar Putri; Ni Made Widisanti S; Sari Rejeki (Universitas Pakuan, 2021)
The objectives of this research are to identify the types and strategies in translating idioms used in Paula Hawkins' novel The Girl on the Train. The research methodology applied isdescriptive qualitative.The results show that the types of idioms (O’Dell and McCarthy 2010)found in the novel are similes, binomials, proverbs, euphemisms, cliché, and fixed statement and other language. Using the theory by Baker (2011), the idioms in the novel are mainly translated using the strategy; translation by phrase. Other strategies that are also applied are using idioms of similar meanings but dissimilar forms, using idioms of singular and form, translating by omission of entire idioms, and borrowing the source language. Keywords: Idioms; Translation Strategy.